2007
DOI: 10.1007/s00213-006-0675-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TC-1734 (AZD3480), a selective neuronal nicotinic receptor agonist, on cognitive performance and the EEG of young healthy male volunteers

Abstract: These early data in healthy subjects provide encouragement to consider development of AZD3480 as a novel agent for the treatment of cognitive decline in the elderly, including age-associated memory impairment and/or dementia of the Alzheimer's type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 42 publications
1
71
1
1
Order By: Relevance
“…The α4β2* receptor agonist, TC-1734, led to an acceleration of the alpha centroid and alpha peak and decreased slow wave activity in young, healthy, male volunteers (Dunbar et al 2007), arguing for an involvement of this nAChR subtype in EEG modulation. However, it has to be noted that this has been an exploratory study and that no statistical correction for multiple testing has been applied.…”
Section: Cholinergic Receptor Subtypes and Vigilance Regulation-influmentioning
confidence: 99%
“…The α4β2* receptor agonist, TC-1734, led to an acceleration of the alpha centroid and alpha peak and decreased slow wave activity in young, healthy, male volunteers (Dunbar et al 2007), arguing for an involvement of this nAChR subtype in EEG modulation. However, it has to be noted that this has been an exploratory study and that no statistical correction for multiple testing has been applied.…”
Section: Cholinergic Receptor Subtypes and Vigilance Regulation-influmentioning
confidence: 99%
“…Strongly dependent on glutamatergic signaling, MMN is attenuated in rats, monkeys and healthy adults with high-affinity NMDA (N-methyl-Daspartate)-type glutamate receptor antagonists (Javitt et al, 1996;Tikhonravov et al 2008;Umbricht et al 2000) such as ketamine which, when combined with nicotine, fails to disrupt MMN in some but not all investigations (Mathalon et al 2014). Most frequently investigated in healthy participants with frequency deviants, nicotinic stimulation has resulted in negative (Knott et al 2006, diminishing (Knott et al 2009) and enhancing effects on MMN amplitude (Dunbar et al 2007), with the latter positive outcome also being shown with pattern (Baldeweg et al 2006), temporal (Martin et al 2009) and visual deviants . Such response variability is also seen in the relatively few studies in SZ, with nicotine not affecting frequency deviant MMN (Dulude et al 2010;Inami et al 2007), shortening latency of intensity-deviant MMN ) and in our work, "normalizing" durationdeviant MMN by increasing the diminished MMN in patients to a level comparable to that seen in healthy volunteers (Dulude et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One of these partial agonists, AZD3480 enhanced both attention and episodic memory function in healthy volunteers (Dunbar et al, 2007). Similarly, varenicline, which is another partial agonist for the α4β2 nAChR and which is marketed as a treatment for smoking cessation (Rollema et al, 2007), alleviated learning deficits in mice that had been induced by either alcohol administration (Gulick and Gould, 2008) or nicotine withdrawal (Raybuck et al, 2008).…”
Section: α4β2 Nachrmentioning
confidence: 99%